2014
DOI: 10.1093/aob/mcu096
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and enzymatic fractionation of cell walls from Fucales: insights into the structure of the extracellular matrix of brown algae

Abstract: The data provide a global snapshot of the cell wall architecture in brown algae, and contribute to the understanding of the structure-function relationships of the main cell wall components. Enzymatic cross-linking of alginates by phenols may regulate the strengthening of the wall, and sulfated polysaccharides may play a key role in the adaptation to osmotic stress. The emergence and evolution of ECM components is further discussed in relation to the evolution of multicellularity in brown algae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
205
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(212 citation statements)
references
References 68 publications
(101 reference statements)
7
205
0
Order By: Relevance
“…Nonetheless, F. vesiculosus fucoidans are reported to have only Fuc and sulfate groups, therefore the residues found in the KOH extract are not likely to be from fucoidans. Rather, we believe that they are part of the hemicelluloses, which have been hypothesized to exist in brown seaweeds, acting as intermediates between cellulose microfibrils and FCSPs (Deniaud-Bouët et al 2014). Analysis of the monosaccharide composition of the extracts (Table 1) confirms that the H 2 O and CaCl 2 extracts are mainly composed of alginates, with high percentages of uronic acids and low percentages of other non-cellulosic neutral sugars, such as Xyl, Man and Gal.…”
Section: Glycome Profilingmentioning
confidence: 83%
See 1 more Smart Citation
“…Nonetheless, F. vesiculosus fucoidans are reported to have only Fuc and sulfate groups, therefore the residues found in the KOH extract are not likely to be from fucoidans. Rather, we believe that they are part of the hemicelluloses, which have been hypothesized to exist in brown seaweeds, acting as intermediates between cellulose microfibrils and FCSPs (Deniaud-Bouët et al 2014). Analysis of the monosaccharide composition of the extracts (Table 1) confirms that the H 2 O and CaCl 2 extracts are mainly composed of alginates, with high percentages of uronic acids and low percentages of other non-cellulosic neutral sugars, such as Xyl, Man and Gal.…”
Section: Glycome Profilingmentioning
confidence: 83%
“…They have high commercial value derived from their nutritional and pharmaceutical importance, which is associated with their viscosifying properties (Cardozo et al 2007;Stengel et al 2011). Fucoidan is a heterogeneous family of fucosecontaining sulfated polysaccharides (FCSPs) that is thought to play a key role in wall architecture by cross-linking cellulose microfibrils (Deniaud-Bouët et al 2014). Increased research interest on FCSPs, triggered by their bioactive potential such as anticoagulant, antivirus, antitumor, anti-inflammatory, antiviral and antioxidant activities, has revealed an enormous structural complexity (Li et al 2008;Ale et al 2011;Usov and Bilan 2009).…”
Section: Introductionmentioning
confidence: 99%
“…oomycetes) members. Through the course of evolution, this lineage gained new biosynthetic capabilities for cell wall components (Michel et al , 2010), allowing the evolution of cell walls/extracellular matrices that were certainly critical for the generation of complex multicellularity (Michel et al , 2010; Deniaud-Bouët et al , 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The relative abundance of M and G blocks in the macromolecular structure determines structural properties and ainity of alginates for divalent cations. The ainity of some divalent metal cations varies with M:G ratio [2,6,22]. Studies have shown that the ainity of the alginates for cations such as Pb, Cu, Cd, Zn, and Ca increases with a higher content of guluronic acid [23,24].…”
Section: Seaweed Biomassmentioning
confidence: 99%
“…The biosorption capability of algae biomass is mostly related to their cell wall chemical composition, which exhibits a iber-like structure and an amorphous embedding matrix of polysaccharides such as alginates and fucoidan [6]. In brown algae, alginates have a high ainity for divalent cations and sulfated polysaccharides give account of the uptake of trivalent cations [7].…”
Section: Introductionmentioning
confidence: 99%